Mobile Learning “Asmeralda” for Teaching Static Fluid at Senior High Schools - Iman Alkautsar; Mita Anggaryani (Berkala Ilmiah Pendidikan Fisika, 2022)
This study applied Research and Development (R&D) method for developing a mobile learning media for teaching static fluid material, namely "Asmeralda" (Aplikasi Mobile Learning Fisika Fluida). This study aims to assess the feasibility of "Asmeralda" implemented in Physics class. In developing "Asmeralda", this study follows the ADDIE steps: Analysis, Design, Development, Implementation, and Evaluation. The data collection used questionaries and interviews. The participants in this study consist of expert lecturers and senior high school students in Surabaya. The results show a positive response towards "Asmeralda" as mobile-based learning media for teaching static fluid. The average feasibility assessment according to expert lecturers as media validators: the material is 91% very feasible, the media is 92.8% very feasible, and the assessment is 91.7% very feasible. The media, according to students, is 92% feasible, 94% practical, and 90% effective. Based on these results, it can be concluded that the mobile-based learning media "Asmeralda" is feasible for teaching static fluid material at Senior High School. However, this conclusion is based on one case in one school in Surabaya. Further study in implementing Asmeralda and mobile learning is crucial for a better strategy in developing media-based computer information.